Elevated blood favipiravir levels are inversely associated with ferritin levels and induce the elevation of uric acid levels in COVID-19 treatment: A retrospective single-center study. Issue 1 (January 2022) - Morikawa, Go; Kubota, Ken; Kondo, Daichi; Takanashi, Yasuhisa; Minami, Satoshi; Kinjo, Tsunemichi; Moriiwa, Yukiko; Yanagida, Akio; Okazawa, Katsuko; Chiaki, Tomoshige
Abstract: Introduction: Measurement of blood Favipiravir (FPV) levels and accumulation of data in COVID-19 patients are critical for assessing FPV efficacy and safety. We performed a retrospective study based on measurements of blood levels of FPV and related factors in COVID-19 patients admitted to our hospital. Furthermore, we also investigated the association between blood FPV levels and uric acid level alterations before and after FPV administration. Methods: We enrolled 27 COVID-19 patients who had received FPV treatment at Hokushin General Hospital from April 1 to December 31, 2020. Age, gender, COVID-19 severity, presence of comorbidities, and laboratory data for each subject were investigated to identify factors that correlate with blood FPV levels. Uric acid levels were measured before and after FPV administration and a difference between the levels ( i.e., a change of uric acid level) was evaluated. Results: When a significant univariate variable was input by the stepwise method and a combination of variables that maintained statistical superiority was searched, serum ferritin was the only factor that independently affected blood FPV level. Furthermore, in the high-FPV group (20 μg/mL or more), a significant increase in uric acid levels was observed after FPV administration. The increment value was significantly larger than that in the low-FPV group (less than 20 μg/mL). Conclusions: Ferritin level was an important independent factor inversely affecting blood FPV level. Furthermore, a high blood FPV level induced the elevation of uric acid levels in COVID-19 treatment.